2022
DOI: 10.1039/d1sd00024a
|View full text |Cite
|
Sign up to set email alerts
|

Layered macrocycles with flexibility and tunable dynamic properties for wide-range thermoresponsive color changes

Abstract: A new flexible layered material was generated from macrocycles containing functional, flexible, and intercalating units. The layered macrocycles exhibit thermoresponsive color changes in a wide temperature range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Our previous work showed that the intercalation of the guest molecules formed the topochemically polymerizable layered structure by shortening the distance between the DA moieties through the conformational changes (Figure 1b). [ 47 ] However, the exfoliation was not studied in the previous work. Here 2‐methoxybenzylamine (2‐OMe‐BA) was used as a guest.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work showed that the intercalation of the guest molecules formed the topochemically polymerizable layered structure by shortening the distance between the DA moieties through the conformational changes (Figure 1b). [ 47 ] However, the exfoliation was not studied in the previous work. Here 2‐methoxybenzylamine (2‐OMe‐BA) was used as a guest.…”
Section: Resultsmentioning
confidence: 99%
“…PDA can be easily coated on a variety of substrates, such as paper, glass, and polymer substrates. 48,55,56,[59][60][61] We have developed the coating methods, such as deposition from the solution phase, 59 dipping in the precursor solution, 48,55,56 precipitation from the colloidal liquid, 60 and spraying of the precursor solution, 61 in previous works. Moreover, the stimuli responsivity was tuned by the intercalated guests in the interlayer space.…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli-responsive color-change properties of PDA have been applied to the development of sensing materials. In general, the self-organized structures of DA monomers, such as vesicles and layered structures, provide PDA through the topochemical polymerization with the irradiation of UV light when the distance between the DA moieties is shorter than 0.5 nm in the condensed states . Molecular design, such as changes in the functional groups, chain lengths, and molecular shapes, has been studied in previous works. However, the structural flexibility sufficient to enhance the dynamic properties with molecular motion is not easily achieved by the topochemically polymerizable self-organized structures containing the densely packed molecules. New approaches that are alternatives to typical molecular design are required to achieve both formation of the self-organized structures and enhancement of the dynamic properties.…”
Section: Introductionmentioning
confidence: 99%